The origins of the Platonic approach to monetary systems: Retracing European and Chinese monetary thoughts on Chartalism, Nominalism, and the origins of monetary systems - Éric Tymoigne (Levy Economics Institute of Bard College, 2024)
A monetary approach that combines Chartalism, Nominalism, and Command origins of monetary systems is often deemed to have emerged only recently, while the Aristotelian approach (Commodity, Metallism, and Market origins of monetary systems) is the only one that existed until the end of the eighteenth/early-nineteenth century. In the major studies of the history of monetary thought, the Chartalism-Nominalism-Command approach is mostly left unmentioned, or at best reduced to an incoherent banality. The paper shows that this approach has a long and rich intellectual history among European monetary thinkers. In Europe, Plato was its first exponent, albeit in a very rudimentary way, and so one may call it the "Platonic approach." It is developed by Roman legists (such as Javolenus, Paulus, and Ulpian) and Medieval legists (such as Du Moulin, Hotman, and Butigella) who note that coins are similar to securities and that debts are serviced when nominal sums are paid rather than specific coins tendered. During the Renaissance and early modern period, a series of scholars and financial practitioners (such as Law, Dutot, Thomas Smith, and James Taylor) emphasize the financial logic behind monetary mechanics and the similarity of coins and notes. In the twentieth century, authors such as Innes, Knapp, Keynes, and Commons build onto the groundwork provided by these past scholars. In China, the Chartalism-Nominalism-Command approach develops independently and dominates from the beginning under Confucian and Legist thoughts. They emphasize the statecraft origins of monetary systems, the role of tax redemption, and the irrelevance of the material used to make monetary instruments. Clay, lead, paper, iron, copper, and tin are normal and convenient means to make monetary instruments, they are not special/emergency materials. The essence of a monetary instrument is not defined by its materiality but rather by its chartality, that is, by the promise it embeds. The Platonic approach rejects the categories and conceptualizations used by the Aristotelian approach and develops new ones, which leads to a different set of inquiries and understanding of monetary phenomena, problems, and history.
Keywords: B10; B11; B20; B26; E42; E62; G12; H30; K15; 330; History of monetary thoughts; monetary theory; Chartalism; Nominalism; asset pricing; redemption